Collaborative music-making: special educational needs school assistants as facilitators in performances with accessible digital musical instruments - Lindetorp, Hans; Svahn, Maria; Hölling, Josefine; Falkenberg, Kjetil; Frid, Emma (Frontiers in Computer Science, 2023)
The field of research dedicated to Accessible Digital Musical Instruments (ADMIs) is growing and there is an increased interest in promoting diversity and inclusion in music-making. We have designed a novel system built into previously tested ADMIs that aims at involving assistants, students with Profound and Multiple Learning Disabilities (PMLD), and a professional musician in playing music together. In this study the system is evaluated in a workshop setting using quantitative as well as qualitative methods. One of the main findings was that the sounds from the ADMIs added to the musical context without making errors that impacted the music negatively even when the assistants mentioned experiencing a split between attending to different tasks, and a feeling of insecurity toward their musical contribution. We discuss the results in terms of how we perceive them as drivers or barriers toward reaching our overarching goal of organizing a joint concert that brings together students from the SEN school with students from a music school with a specific focus on traditional orchestral instruments. Our study highlights how a system of networked and synchronized ADMIs could be conceptualized to include assistants more actively in collaborative music-making, as well as design considerations that support them as facilitators.